Flexible, adhesive, strain‐sensitive, and skin‐matchable hydrogel strain sensors for human motion and handwritten signal monitoring. (19th October 2022) - Zhao, Chunxia; Chen, Yunxin; Guo, Min; Wu, Yuanpeng; Li, Yuntao; Xiang, Dong; Li, Hui; Wang, Li; Sun, Zhe
Abstract: Flexible hydrogel strain sensors have made great progress in medical applications, human motion detection, and human‐machine interactions. However, the design of hydrogels to realize the synergistic responses of excellent mechanical properties, robust adhesion, and stable sensing is still a highly challenging task. Herein, we report a multifunctional hydrogel (PAMT hydrogel) by crosslinking acrylic acid (AA), 2‐methacryloyloxyethyl phosphorylcholine (MPC) and tannic acid (TA) to form a polymer network via a simple one‐pot free radical polymerization. Among them, the dynamic bonding with hydrogen bonding between PAA chains and TA significantly improved the stretch ability of the hydrogels (700%), and the abundant catechol groups on TA endowed the hydrogels with strong and stable adhesion properties (the adhesion strength to glass reached 248 N m −1 ). When applied to human skin, the hydrogel can be easily peeled off without leaving any residue. Furthermore, the strain sensor assembled using PAMT hydrogel could not only effectively detect the movement in different parts of the human body, but also be used for precise handwritten recognition and electric skin of silicone prosthetic hand. Due to the addition of MPC and TA, the conductive hydrogel has good biocompatibility and no harm to human body. Therefore, PAMT hydrogel has opened up a new vision for the development of intelligent detection and bionic intelligent robots.